(2,2′-Bipyridine-6,6′-dicarboxylato-κ3N,N′,O6)(6′-carboxy-2,2′-bipyridine-6-carboxylato-κ3N,N′,O6)cobalt(III) - Huimin Wang; Xiaojun Gu; Bingbing Zhang; Haiquan Su (Acta Crystallographica Section E, 2012)
The CoIII atom in the title compound, [Co(C12H6N2O4)(C12H7N2O4)], is six-coordinated in a distorted octahedral geometry by four N atoms and two O atoms of the chelating 2,2′-bipyridine-6,6′-dicarboxylate and 6′-carboxy-2,2′-bipyridine-6-carboxylate ligands. Intermolecular O—H...O hydrogen bonds and face-to-face π-stacking interactions [centroid–centroid distance = 3.6352 (16) Å] between inversion-related pyridine rings link adjacent mononuclear units into a two-dimensional supramolecular structure, and several intermolecular C—H...O interactions are also observed.